2010
DOI: 10.1073/pnas.1010377108
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of global genome nucleotide excision repair by SIRT1 through xeroderma pigmentosum C

Abstract: Disruption of the nucleotide excision repair (NER) pathway by mutations can cause xeroderma pigmentosum, a syndrome predisposing affected individuals to development of skin cancer. The xeroderma pigmentosum C (XPC) protein is essential for initiating global genome NER by recognizing the DNA lesion and recruiting downstream factors. Here we show that inhibition of the deacetylase and longevity factor SIRT1 impairs global genome NER through suppressing the transcription of XPC in a SIRT1 deacetylase-dependent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(142 citation statements)
references
References 70 publications
10
125
0
7
Order By: Relevance
“…Acetylation of PTEN has been shown to inhibit its activity and thus activate AKT (35,36). We used immunoblotting analysis in the same cellular models as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation of PTEN has been shown to inhibit its activity and thus activate AKT (35,36). We used immunoblotting analysis in the same cellular models as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DNA repair is a crucial cellular pathway that autonomously maintains genome integrity and previously known to be regulated by SIRT1 (37,38). Among various types of repair mechanisms, our study showed that SIRT1 may play a profound role in regulating base excision repair (BER) and mismatch repair (MR), two types of single-strand DNA repair mechanisms.…”
Section: Analysis Of Dynamics In Protein Domains By Sirt1mentioning
confidence: 83%
“…SIRT1 deacetylates two lysines of the core NER protein XPA (xeroderma pigmentosum group A); this reaction is necessary for the full efficiency of UV damage removal [50]. SIRT1 also relieves the repression of the XPC gene coding for a protein that recognizes DNA lesion and recruits other NER components [135]. Table II.…”
Section: Sirtuins and Dna Repairmentioning
confidence: 99%